Keanekaragaman Serangga Berpotensi Penyerbuk pada Tanaman Jambu Biji (Psidium guajava L.) - Della Ivanka; Puji Prastowo (Biocaster : Jurnal Kajian Biologi, 2026)
Pollinator insects have an important role in the success of plant reproduction, but information on the diversity of pollinating insects in guava plants in Tanjung Anom Village is still limited. This study aims to determine the diversity, dominance, distribution pattern, and differences in the presence of potentially pollinating insects in guava plants (Psidium guajava L.) between morning and evening in Tanjung Anom Village, Pancur Batu District, Deli Serdang Regency. The research was carried out from June to August 2025. The selection of sample trees was carried out by purposive sampling, while the observation of pollinating insects used the scan sampling method which was carried out four times with an interval of one week in the morning and evening. The results of the study show that there are nine species of insects with potential pollinators that belong to three orders and four families. The level of diversity is classified as moderate (H' morning = 1.80; H' afternoon = 2.08), while the dominance level was low (C morning = 0.16; C afternoon = 0.11). Distribution pattern analysis showed that five species had a grouping pattern, namely Ischiodon scutellaris, Apis cerana, Tetragonula laeviceps, Xylocopa confusa, and Nomia sp., while four species showed a uniform distribution pattern, namely Anomala sp., Eumerus sp., Apis dorsata, and Xylocopa latipes. The results of the t-test showed a significant difference in the presence of pollinating insects between morning and evening with a p value of < 0.05. These findings show that the difference in the time of daily activity affects the structure of the pollinating insect community in guava plants. Therefore, the results of this study can be used as the basis for agroecosystem management, especially in the regulation of cultivation practices to increase pollination effectiveness and plant productivity.